Ergonomic evaluation in product design for surgical instruments traceability - Sampaio, Álvaro M. (2011)
Health care providers have been continuously increasing their interest in tracking products. The plethora of goods that they need, the number of persons involved and the enormous space that they have makes an imperative to manage and control everything. In most cases, health care providers are labelling all products with technologies that can range from bar-coding to RFID. However, the great variety in terms of items to track (shape, material, size, etc) limits the adoption of such technologies. In some cases, existing products are fully optimized and any changes, even small ones, are impossible. This is the case of surgical instruments. Incorporating RFID in surgical instruments is not trivial, as moisture, metal surfaces and temperature can affect the tag reliability, and the surgical instruments have very demanding requirements, having been optimized over decades (or centuries) for specific applications, our first approach to achieve an instrument traceability solution was the development of a polymer-based add-on product that features an embedded RFID, and which could be coupled to the surgical instrument. To ensure that the placement of the RFID tag does not hamper or limit the performance of the health professional using the surgical instrument, it was necessary to conduct an ergonomic evaluation to investigate the contact points between the surgeons’ hands and the surgical instruments. In this framework, we have conducted a survey with 54 surgeons to discover the contact points with 7 different types of surgical instruments that covers a major generic set (72 surgical instruments), and we describe how it was employed in the creation of a design solution. Future work includes prototyping parts, with the embedded RFID tag, and usability tests. The developed product should allow for a fast and accurate count during surgical and sterilizing operations, and, at the same time, knowing the number of uses of each instrument, as well as the specific set to which the instrument belongs. This system can help prevent several typical errors, such as miscounting, misplacement or the accidental disposal of instruments.